PENGARUH VARIASI PERSENTASE BUBUK CANGKANG TELUR (BCT) SEBAGAI BAHAN PENAMBAH SEMEN TERHADAP KUAT TEKAN DAN ABSORPSI MORTAR - Syahwati, Manis; Wahyuni, Ade Sri (Inersia: Jurnal Teknik Sipil, 2019)
Eggshell powder is obtained from crushed dried eggshell waste. Egg shells contain 97% calcium carbonate. The large calcium content has the potential to be used in cement. This study aims to determine the compressive strength and absorption of mortar by adding 2,5% to 15% eggshell powder with a range of 2,5%. The method of manufacture and test compressive strength and absorption of the mortar refers to SNI 03-6825-2002 and SNI 15-2049-2004. The total of mortar cubes are 84 pieces with dimensions 50 mm. Each variation has 8 mortar cubes for compressive strength and 4 mortar cubes for absorption. The range of initial flow values used are 105%-115%. Mortar cubes soaked for 26 days and test of mortar conducted at 28 days. The highest value of mortar compressive strength occurred in addition 12,5% eggshell powder (13,49 Mpa) with increased percentage of 22,04% from the normal mortar. The smallest value of mortar absorption occurred in addition 12,5% eggshell powder (8,76%).